Patterns and contextual determinants of antibiotic prescribing for febrile under-five outpatients at primary and secondary healthcare facilities in Bugisu, Eastern Uganda. Issue 5 (5th September 2022) - Allwell-Brown, Gbemisola; Namugambe, Juliet Sanyu; Ssanyu, Jacquellyn Nambi; Johansson, Emily White; Hussain-Alkhateeb, Laith; Strömdahl, Susanne; Mårtensson, Andreas; Kitutu, Freddy Eric
Abstract: Objectives: To describe patterns and contextual determinants of antibiotic prescribing for febrile under-five outpatients at primary and secondary healthcare facilities across Bugisu, Eastern Uganda. Methods: We surveyed 37 public and private-not-for-profit healthcare facilities and conducted a retrospective review of antimicrobial prescribing patterns among febrile under-five outpatients (with a focus on antibiotics) in 2019–20, based on outpatient registers. Multilevel logistic regression analysis was used to identify determinants of antibiotic prescribing at patient- and healthcare facility-levels. Results: Antibiotics were prescribed for 62.2% of 3471 febrile under-five outpatients. There were a total of 2478 antibiotic prescriptions of 22 antibiotic types: amoxicillin (52.2%), co-trimoxazole (14.7%), metronidazole (6.9%), gentamicin (5.7%), ceftriaxone (5.3%), ampicillin/cloxacillin (3.6%), penicillin (3.1%), and others (8.6%). Acute upper respiratory tract infection (AURTI) was the commonest single indication for antibiotic prescribing, with 76.3% of children having AURTI as their only documented diagnosis receiving antibiotic prescriptions. Only 9.2% of children aged 2–59 months with non-severe pneumonia received antibiotic prescriptions in line with national guidelines. Higher health centre levels, and private-not-for-profit ownership (adjusted OR, 4.30; 95% CI, 1.91–9.72) were significant contextual determinants of antibiotic prescribing. Conclusions: We demonstrated a high antibiotic prescribing prevalence among febrile under-five outpatients in Bugisu, Eastern Uganda, including prescriptions for co-trimoxazole and ampicillin/cloxacillin (which are not indicated in the management of the common causes of under-five febrile illness in Uganda). Study findings may be linked to limited diagnostic capacity and inadequate antibiotic availability, which require prioritization in interventions aimed at improving rational antibiotic prescribing among febrile under-five outpatients.